Calvin - Gordon, Bruce, 1962- (New Haven, Conn. : Yale University Press, 1953)
Biografie van Calvijn, de grondlegger van het calvinisme.
The book explores with particular insight Calvin's self-conscious view of himself as prophet and apostle for his age and his struggle to tame a sense of his own superiority, perceived by others as arrogance. Gordon looks at Calvin's character, his maturing vision of God and humanity, his personal tragedies and failures, his extensive relationships with others, and the context within which he wrote and taught. --from publisher description
Keywords: Calvin, Jean, -- 1509-1564